2020
DOI: 10.1155/2020/8745472
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude, and Practice in respect of Medical Waste Management among Healthcare Workers in Clinics

Abstract: Medical waste represents a significant health risk and an environmental pollution concern due to its hazardous characteristics. The knowledge and practice of healthcare personnel in respect of the disposal of medical waste is essential to perform effective medical waste management. Therefore, the aim of this study was to assess the knowledge, attitudes, and practices related to medical waste management among healthcare workers in clinics (medical and dental clinics, specialized medical, laboratory clinics, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
47
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 15 publications
12
47
8
2
Order By: Relevance
“…Among them, those with the highest number of favorable attitudes were physicians (89%) and nurses (78%). This was supported [ 22 , 28 , 29 ] by a study in India, at a tertiary level healthcare institution, where doctors (100%) were found to be more positive towards the need for actions for safe biomedical waste management than nurses (60%) and other healthcare workers [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…Among them, those with the highest number of favorable attitudes were physicians (89%) and nurses (78%). This was supported [ 22 , 28 , 29 ] by a study in India, at a tertiary level healthcare institution, where doctors (100%) were found to be more positive towards the need for actions for safe biomedical waste management than nurses (60%) and other healthcare workers [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…29 Knowledge was found to be less compared to other study of Ethiopia, where 83.9% doctors had knowledge about the correct ways of segregation of waste. 18 In our study, we found that there were gaps in knowledge about the fate of the waste after it was segregated, followed by how were they treated and the safe transportation of biomedical waste from the hospital. This is comparable to another study where knowledge score was 64% amongst students 30 .…”
Section: Discussionmentioning
confidence: 83%
“…17 In a study in Thailand conducted to assess the knowledge of medical professionals regarding BMW management, the overall scores were found to be at a higher level (89.5%). 18 Similarly, the average knowledge score in three Low-and Middle-Income countries Ethiopia, Nigeria and Sri Lanka were found to be 56.8%, 45% and 40.5% , respectively. 19 , 20 , 21 The improper disposal of COVID-19 bio-medical waste poses severe risks to public health and the environment as it acts as a host of variety of pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 91%
“…Akkajitet al [ 26 ] suggest that people's attitudes influence their behaviour towards waste disposal, for example, in terms of demand for waste collection services. This was verified with respect to willingness to pay for solid waste collection services.…”
Section: Resultsmentioning
confidence: 99%